Economic Stabilization Policy : methods in optimization - Friedman, Benjamin M. (Amsterdam : North-Holland Publishing Company ; New York : American Elsevier, 1975)
In this book, the author starts with a known theoretical framework for decision-making. He relaxes some of its restrictive assumptions such as the linearity of the constraints and the quadratic form of the criterion function. He then applies the framework thus generalized to the Wharton model of the U.S. economy in order to analyze alternative strategies for economic stabilization in detailed numerical form.
An expansion of the author's thesis, Harvard.
Includes index.
Includes bibliographical references: p. 359-367.
ne 08/06/2018
Loans
Keywords: Economic stabilization; Mathematical optimization